Enhancing Students’ English Skill through the Implementation of Project-Based Learning: Enhancing Students’ English Skill through the Implementation of Project-Based Learning - Siti Khikmiyah miyah (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
This study was conducted to obtain data and information about the effectivity of project-based learning on students’ English skill. This research was conducted at Islamic Institute of Uluwiyah Mojokerto consisting of Islamic family law and Islamic religious education majors. This research was quasi-experimental research that uses a project-based learning model as a treatment. The sample was 60 students taken from two majors. Both of majors consisted of 30 students. The hypothesis was analyzed statistically by SPSS 20 program using independent t-test analysis. The results of data analysis showed that the sig-value 0.004 is smaller than 0.05 as the significant level. Thus, it can be concluded that the implementation of project-based learning model was effective on students’ English skill.